Algunos constituyentes de Uncaria Guianensis - Alvarez Agüero, Carmen María (1988)
Mitraphylline, a pentacyclic oxindolc alkaloid, has bcen isolatcd fromthe leaves of Uncaria guimensis. Furthermore, seven phenolic compounds ha-ve lxen detccted as being present in thc bark of this plant; two of them wereseparatcd as glycosides and isolated as aglycones; we propose the structures ofkaernpherol and dihydrokaempherol for them.